2022
DOI: 10.1177/00332941221129131
|View full text |Cite
|
Sign up to set email alerts
|

Research of the Coronavirus Anxiety, Post-Traumatic Stress, Generalized Anxiety Disorder, Quality of Life, and Stress Coping Styles in COVID-19 Survivors

Abstract: The COVID-19 survivors suffer from severe psychosocial challenges related to the current pandemic. In this context, it was aimed to evaluate the coronavirus anxiety, generalized anxiety disorder (GAD), and post-traumatic stress symptoms (PTSS) and also determine the quality of life (QOL), and coping styles with stress in survivors by comparing them with non-COVID controls (NCs). This study was conducted from April 15 to October 15, 2021, as a cross-sectional study design. The study included 339 survivors who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
3
0
3
Order By: Relevance
“…Improving the treatment environment in isolation areas, providing as much stimulation as possible during the normal routine of work and rest, establishing a good lifestyle, and diversifying hospital activities are of great significance in relieving emotional tension, breaking psychological barriers, and promoting disease recovery 24 . Studies have shown that having sufficient sunlight is particularly effective for psychological relief 25 . Isolation areas should be set up to face south, and lighting measures should be strengthened.…”
Section: Discussionmentioning
confidence: 99%
“…Improving the treatment environment in isolation areas, providing as much stimulation as possible during the normal routine of work and rest, establishing a good lifestyle, and diversifying hospital activities are of great significance in relieving emotional tension, breaking psychological barriers, and promoting disease recovery 24 . Studies have shown that having sufficient sunlight is particularly effective for psychological relief 25 . Isolation areas should be set up to face south, and lighting measures should be strengthened.…”
Section: Discussionmentioning
confidence: 99%
“…A amostra final foi composta por seis artigos, onde todos estavam no idioma inglês. Além disso, destaca-se que as pesquisas foram conduzidas em diferentes regiões do mundo, como Polônia (Florek, 2023;Shpakou et al, 2022), Áustria (Lueger-Schuster et al, 2022), Espanha (Osses-Anguita et al, 2023) e Turquia (Korkut et al, 2022), Qatar (Abbas et al, 2023).…”
Section: Fonte: Autores (2023)unclassified
“…Os autores Abbas et al (2023) e Korkut et al (2022) compartilham conclusões semelhantes sobre os efeitos psicológicos da pandemia. Ambos destacam um aumento em desafios de saúde mental além da ansiedade, como ausências escolares, uso excessivo de substâncias, perturbações do sono e transtornos alimentares.…”
Section: Fonte: Autores (2023)unclassified
“…Previous studies have reported an increase in anxiety among older adults and a high incidence of COVID-19 anxiety in the elderly following the outbreak. [7][8][9] Advanced age is associated with various diseases and disorders, including mental health conditions, with anxiety being one of the most prevalent. 10 Anxiety significantly affects the lives of the elderly, reducing their quality of life, 11 increasing the risk of developing dementia 12 and cardiovascular diseases, 13 and impairing cognitive function, overall functioning, and sleep patterns.…”
Section: Introductionmentioning
confidence: 99%
“…COVID‐19 anxiety and geriatric anxiety have emerged as negative consequences following the pandemic. Previous studies have reported an increase in anxiety among older adults and a high incidence of COVID‐19 anxiety in the elderly following the outbreak 7–9 . Advanced age is associated with various diseases and disorders, including mental health conditions, with anxiety being one of the most prevalent 10 .…”
Section: Introductionmentioning
confidence: 99%